CIVILIAN APPLICATION OF LIQUID PROPELLANT ROCKET MOTOR PRINCIPLE (Advances in Military Technology, 2022)
The paper deals with application of liquid propellant rocket motor possibilities for civilian exploitation as e.g. for the solution of steam gas for the steam turbines drive. These questions are in the time being very important mainly with respect to the so called clean energy sources.One of several possibilities how to get such "clean energy system" source is the utilisation of convenient fuels and oxidisers combustion inside the gas generator combustion chamber, the majority of which are in gaseous state and designed at the base of liquid propellant rocket motor.